Strengthening Good Governance through the Optimization of the Institutional Functions of the Secretariat of the Batam City DPRD in the Era of Bureaucratic Reform - Wahyu Fery Dian; Sapto Pramono; Dandy Wirawan; Sri Roekminiati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
The Secretariat of the Regional People's Representative Council (DPRD) is a strategic institutional unit that determines the quality of local legislative function implementation. The implementation of good governance principles in this unit is a fundamental prerequisite for realizing a regional legislative institution that is accountable, transparent, and responsive to public needs. This study uses a qualitative approach with data collection techniques consisting of in-depth interviews, passive participant observation, and document review. Informants were selected through purposive sampling involving seven informants, consisting of the DPRD Secretary, three Heads of Division, one Senior Policy Analyst, one DPRD Member, and one representative of a monitoring institution. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña (2014), while data validity was ensured through source and technique triangulation. The findings show that the implementation of good governance at the Secretariat of the Batam City DPRD remains at the developing stage, with a positive but not yet optimal improvement trend. The five dimensions of good governance examined—transparency, accountability, responsiveness, effectiveness and efficiency, and participation—all show gaps between ideal regulatory conditions and actual implementation in the field. The main inhibiting factors include human resource competency mismatches, limited digital infrastructure, lengthy bureaucratic procedures, weak institutional coordination, and an organizational culture that is not yet innovation-oriented. Based on these findings, a four-pillar strategy for strengthening good governance is formulated: competency-based human resource capacity strengthening, acceleration of digital transformation, strengthening of coordination mechanisms and public participation, and organizational culture transformation. This study contributes to the development of regional legislative institutional literature, particularly studies on good governance in DPRD Secretariats in nationally strategic areas.